Polyphosphate-kinase-1 dependent polyphosphate hyperaccumulation for acclimation to nutrient loss in the cyanobacterium, Synechocystis sp. PCC 6803 - Sato, Norihiro; Endo, Mizuki; Nishi, Hiroki; Fujiwara, Shoko; Tsuzuki, Mikio (Frontiers in Plant Science, 2024)
Polyphosphate is prevalent in living organisms. To obtain insights into polyphosphate synthesis and its physiological significance in cyanobacteria, we characterize sll0290, a homolog of the polyphosphate-kinase-1 gene, in the freshwater cyanobacterium Synechocystis sp. PCC 6803. The Sll0290 protein structure reveals characteristics of Ppk1. A Synechocystis sll0290 disruptant and sll0290-overexpressing Escherichia coli transformant demonstrated loss and gain of polyphosphate synthesis ability, respectively. Accordingly, sll0290 is identified as ppk1. The disruptant (ppk1) grows normally with aeration of ordinary air (0.04% CO2), consistent with its photosynthesis comparable to the wild type level, which contrasts with a previously reported high-CO2 (5%) requirement for ppk1 in an alkaline hot spring cyanobacterium, Synechococcus OS-B'. Synechocystis ppk1 is defective in polyphosphate hyperaccumulation and survival competence at the stationary phase, and also under sulfur-starvation conditions, implying that sulfur limitation is one of the triggers to induce polyP hyperaccumulation in stationary cells. Furthermore, ppk1 is defective in the enhancement of total phosphorus contents under sulfur-starvation conditions, a phenomenon that is only partially explained by polyP hyperaccumulation. This study therefore demonstrates that in Synechocystis, ppk1 is not essential for low-CO2 acclimation but plays a crucial role in dynamic P-metabolic regulation, including polyP hyperaccumulation, to maintain physiological fitness under sulfur-starvation conditions.